The Nomad and the Couch Potato: Enriching Mobile Shared Experiences with Contextual Information - Kim, Seungwon; Junuzovic, Sasa; Inkpen, Kori (Group 2014, 2014)
Mobile videoconferencing is increasingly being used to bring remote friends or family along to an activity happening outside the home, such as shopping or visiting a tourist attraction. We explored how including contextual information of the event, in addition to audio and video of the person at the event, impacts the shared experience. We studied three kinds of information: a map showing the position of the person at the activity, a second live video showing what was in front of that person, and a history of periodic high quality images showing what was in front of the person. We carried out a field study with twelve pairs of participants, where one participant (the nomad) was at a self-selected activity while the other (the couch potato) joined the activity from our lab. The study results show that including contextual information significantly improved connectedness and the sense of presence for both participants. Each kind of contextual information offered unique benefits. The map was used for orientation and to provide directions, the second live video for “do you see this” moments and to maintain a sense of liveliness, and the image history for “did you see that” moments and to see greater detail. Together they led to smooth view negotiation, activity input from the couch potato, and high levels of engagement.